Intikhab-e-Kalam : Wali - Wali Deccani; Edited and introduced by Zafar Iqbal (Karachi Oxford University Press, 2016)
Seventeenth century was proved to be the starting point of the blossoming era of the Urdu poetry. Vali (1667-1707) was the most prominent north Indian Urdu poet of that era. He forms a link between the Deccani poets who wrote in the southern dialect, and the poets of Delhi, who wrote in the northern dialect, which was more Persianised. Vali's poetry gave thus the spur to other poets of Delhi. His Divan became the trendsetter for other poets. Most of his poetry consists of Ghazals but his Divan also includes Rubai, Naat, Mukhammis etc. He represented the dying culture of Mughal civilization. He was the first Urdu poet who stylistically mixed Persian with Hindi in his poetry. His most favorite themes were mystical and earthly love. He is also known as the architect of the modern poetic language which is the blend of Persian and Hindi vocabulary.
Keywords: Urdu Literature - Poetry -- Poetry in Urdu -- Urdu Literature - Poetry -- Intikhab e Kalam : Wali Mohammed Wali -- Intikhab e Kalam : Wali Deccani